Pengaruh Inovasi Layanan terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan sebagai Variabel Intervening (Management Analysis Journal, 2015)
Business competition in the corporate world encourage a company can become a winner in their business competition. This circumstances resulted in company tried to retain their customers by making service innovation. The purpose of this study was to determine the effect on customer loyalty either directly or indirectly. The sampling uses accidental sampling technique with a total of 96 respondents. The data collection methods of this study was questionnaires. The data analysis used in this study was descriptive analysis, classical assumption and path analysis through SPSS program. The result of this research known that the customer satisfaction mediates the effect of service innovation to customer loyalty. The conclusion of this study is service innovation effect on customer loyalty directly and indirectly, so that it can be explained that the higher level of customer satisfaction from the impact of service innovation created, it will be able to increase customer loyalty.